The potential of Pseudomonas for bioremediation of oxyanions - Vieto Fonseca, Sofía (2021)
Non-metal, metal and metalloid oxyanions occur naturally in minerals and rocks of the Earth’s crust and are mostly found in low concentrations or confined in specific regions of the planet. However, anthropogenic activities including urban development, mining, agriculture, industrial activities and new technologies have increased the release of oxyanions to the environment, which threatens the sustainability of natural ecosystems, in turn affecting human development. For these reasons, the implementation of new methods that could allow not only the remediation of oxyanion contaminants but also the recovery of valuable elements from oxyanions of the environment is imperative. From this perspective, the use of microorganisms emerges as a strategy complementary to physical, mechanical and chemical methods. In this review, we discuss the opportunities that the Pseudomonas genus offers for the bioremediation of oxyanions, which is derived from its specialized central metabolism and the high number of oxidoreductases present in the genomes of these bacteria. Finally, we review the current knowledge on the transport and metabolism of specific oxyanions in Pseudomonas species. We consider that the Pseudomonas genus is an excellent starting point for the development of biotechnological approaches for the upcycling of oxyanions into added-value metal and metalloid byproducts.